Climate-Related Risk Governance: How Corporate Transparency Influences Market Perception - Rumasukun, Mohammad Ridwan (Journal of Sustainability Industrial Engineering and Management System, 2025)
This study examines how climate-related risk governance and corporate transparency jointly shape market perception by synthesizing contemporary empirical and theoretical developments within the sustainability and climate finance literature. The research aims to clarify the mechanisms through which governance structures influence the quality and credibility of climate disclosures and how these disclosures, in turn, inform investor assessments of firm resilience, strategic preparedness, and long-term value potential. Using a qualitative systematic literature review approach, the study analyzes peer-reviewed research published between 2014 and 2024, drawing on multidisciplinary evidence from accounting, finance, environmental management, and regulatory policy. The results demonstrate that robust climate-risk governance enhances firms’ ability to identify, quantify, and manage climate risks and serves as the internal foundation for producing high-quality and decision-useful disclosures. Furthermore, the findings reveal that transparent climate reporting reduces information asymmetry, strengthens investor confidence, and contributes to more favorable market valuations, particularly when disclosures align with standardized frameworks such as TCFD and IFRS S2. The study also identifies substantial variation in disclosure practices across industries and regions and highlights the risks associated with selective reporting and greenwashing. The findings underscore that governance and transparency are not isolated constructs but mutually reinforcing drivers of market interpretation and sustainable value creation. Overall, this research provides theoretical insight into the governance–transparency–market nexus and offers practical implications for firms, investors, and regulators seeking to advance climate-aligned financial systems.